KETERLIBATAN WANITA DALAM BERPOLITIK - Sukarno, Bedjo (Transformasi, 2011)
Abstrak Women's political democracy has not been as expected, women's political democracy implies only on respect of sovereignty inherent in every human. Involvement of women in the political field has long been a concern of society, because it remains political women to fight for women's rights. Key words: women's involvement in politics, women's political rights